2021
DOI: 10.1136/bmjopen-2020-038880
|View full text |Cite
|
Sign up to set email alerts
|

Exploring physiotherapists’ and occupational therapists’ perceptions of the upper limb prediction algorithm PREP2 after stroke in a rehabilitation setting: a qualitative study

Abstract: ObjectiveTo explore how physiotherapists (PTs) and occupational therapists (OTs) perceive upper limb (UL) prediction algorithms in a stroke rehabilitation setting and identify potential barriers to and facilitators of their implementation.DesignThis was a qualitative study.SettingThe study took place at a neurorehabilitation centre.ParticipantsThree to six PTs and OTs.MethodsWe conducted four focus group interviews in order to explore therapists’ perceptions of UL prediction algorithms, in particular the Predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Thus, caution is needed when applying the EPOS model very early after stroke, especially in those patients who initially have no voluntary upper limb motor function (i.e., the ‘unfavorable’ prognosis group). Since prognostic models for upper limb recovery are implemented increasingly [ 42 , 43 ], this becomes an even more important issue, as the model would misinform therapists and patients in the early false negative prognosis scenario. In the case of an unfavorable prognosis, it recommended to focus on the application of compensational strategies [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, caution is needed when applying the EPOS model very early after stroke, especially in those patients who initially have no voluntary upper limb motor function (i.e., the ‘unfavorable’ prognosis group). Since prognostic models for upper limb recovery are implemented increasingly [ 42 , 43 ], this becomes an even more important issue, as the model would misinform therapists and patients in the early false negative prognosis scenario. In the case of an unfavorable prognosis, it recommended to focus on the application of compensational strategies [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This effort to predict an individual’s subsequent UL performance category is informed by the development of the PREP 2 algorithm [ 19 , 20 ], which has demonstrated that prediction of an UL capacity (i.e. activity a person has the capability to do) category provides clinically-useful information to people with stroke and their families [ 21 24 ]. Advances in computing have improved upon old and led to new analysis techniques for building prediction models of UL outcomes after stroke.…”
Section: Introductionmentioning
confidence: 99%